2022
DOI: 10.1371/journal.pone.0265736
|View full text |Cite
|
Sign up to set email alerts
|

Video-based messages to reduce COVID-19 vaccine hesitancy and nudge vaccination intentions

Abstract: Vaccines are highly effective for curbing the spread of SARS-CoV-2 (COVID-19). Yet, millions of Americans remain hesitant about getting vaccinated, jeopardizing our ability to end the COVID-19 pandemic by fueling the spread and development of new variants. We show that brief video-based messages of encouragement addressing specific COVID-19 vaccine concerns increase vaccination intentions, and that vaccination intentions, in turn, are predictive of future vaccine uptake. Results from our online experiment reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 52 publications
2
64
1
Order By: Relevance
“…Indeed, previous research indicates that revealed intentions, based on participants' clicks, constitute strong predictors of actual behavior (Godin & Kok, 1996;Webb & Sheeran, 2006;de Bruin et al, 2012). Our expectation is also derived from previous research (Jensen et al, 2021), which indicates that up to 90% of individuals keep their vaccination appointments and actually show up (Dai et al, 2021). Following this logic, we estimate that the control letter alone has led to about 908 actual vaccinations and the treatment letter to 1210 actual vaccinations.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, previous research indicates that revealed intentions, based on participants' clicks, constitute strong predictors of actual behavior (Godin & Kok, 1996;Webb & Sheeran, 2006;de Bruin et al, 2012). Our expectation is also derived from previous research (Jensen et al, 2021), which indicates that up to 90% of individuals keep their vaccination appointments and actually show up (Dai et al, 2021). Following this logic, we estimate that the control letter alone has led to about 908 actual vaccinations and the treatment letter to 1210 actual vaccinations.…”
Section: Discussionsupporting
confidence: 73%
“…Given global differences in booster policy, cross-cultural replication of results is required to ensure results are not contextually limited to the UK. While vaccine intention has been demonstrated to be a strong predictor of vaccine uptake (e.g., [51][52][53]), including for COVID-19 vaccination [54], we do not assume that the two are synonymous (e.g., [55]). While beyond the scope of the present study, we recommend that future research incorporate longitudinal designs where the rate of conversion from intention to vaccine uptake can be tracked, as well as consider the effect of framing on those under 18 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the study include the measurement of intention, but not uptake. While intention has been found to predict vaccination [21][22][23][24] , longitudinal research is needed to directly assess the role of framing on actual uptake, as well as the longevity of the framing effect among those yet to receive a booster vaccine. Relevant to the lag in booster uptake in Australia 25 , the present research focused on increasing intention among those already receiving a primary course of COVID-19 vaccination.…”
Section: Secondary-predictors: Mediationmentioning
confidence: 99%